Pemanfaatan Aplikasi Canva Dalam Promosi Usaha Online Di Kota Bengkulu - Wahyuni, Melisa; Yanto, Yanto; Maryaningsih, Maryaningsih (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Canva is an online application that can be used to create graphic designs for various needs such as logos, social media content, banners, posters and flyers. This study aims to describe the utilization of the canva application in online business promotion to increase sales. This research is qualitative research. based on TerenceShimp's Marketing Communication Dimensions Theory (2003). The results of this study indicate that the utilization of the canva application has been effective and has contributed to increasing sales and strengthening marketing strategies for online business owners in the city of bengkulu, especially for MSMEs. The results of individual sales of the canva application are an effective tool for creating attractive and professional promotional materials. Its use includes selecting backgrounds, editing designs with text, images, and other design elements, changing colors, fonts, and layouts as needed. Advertising that Canva has an advantage in creating advertising designs compared to other applications. Sales promotion where Canva helps them create professional designs, increase buyer confidence, build a strong visual identity, and visually communicate product benefits to buyers. Sponsorship marketing where wise use of Canva in a larger marketing strategy can contribute significantly to sales growth and brand awareness, Publicity, Canva provides a useful tool for creating attractive promotional designs. Thus, this strategy can be an effective step in growing the business of the business owner. and communication at the point of purchase Canva application is an invaluable tool for MSMEs and small businesses to improve quality and efficiency in the field of design and promotion.